Letting the deaf Be Deaf: Reconsidering the Use of Cochlear Implants in Prelingually Deaf Children - Crouch, Robert A. (The Hastings Center report, 1997)
In theory, cochlear implants hold out the possibility of enabling profoundly prelingually deaf children to hear. For these children's parents, who are usually hearing, this possibility is a great relief. Yet the decision to have this prosthetic device implanted ought not to be viewed as an easy or obvious one. Implant efficacy is modest and the burdens associated with them can be great. Moreover, the decision to forgo cochlear implantation for one's child, far from condemning her to a world of meaningless silence, opens the child up to membership in the Deaf community, which has a rich history, language, and value system of its own.